Urgensi Penambahan Parameter Potensi Lokal dalam Pengalokasian Formulasi Dana Desa sebagai Upaya Pengembangan Pariwisata Lokal di Indonesia - Puspita Putri Sunarso; Eka Rahmawati; Fazal Akmal Musyarri (Jurnal Hukum Lex Generalis, 2020)
The development of tourism in Indonesia today has increased significantly. Pariwasata is one of the country's sizable foreign exchange income contributors. Indonesia's Gross Domestic Product (GDP) from the tourism sector in 2010 amounted to 261.05 Trillion Rupiah. This figure skyrocketed to 461.36 trillion rupiah in 2015. This is inseparable from the role of large tourism potential in Indonesia. Indonesia is a unitary state consisting of islands that line from Sabang to Merauke that have quite diverse tourism potential. In this stretch of Indonesia, there is the smallest unit of society called a village. The village is regulated in Law No. 16 of 2014 concerning Villages. The village is the smallest part of a region that has certain potentials that can be developed not only based on its geographical circumstances. But it can also take advantage of the sociological and anthropological conditions of society. For example, villages located in coastal areas can develop tourism potential for aquaculture and aquatic resources. While villages located in mountainous areas can develop tourism potential in the form of ecotourism-based education. The village tourism sector can also be developed from the rich culture that lives among the people. But over time, problems arise in tourism management efforts. The problem is the lack of optimal role of the government in managing tourism potential, especially in the village. On the other hand, in order to optimize the authority of the village as the smallest government order authorized to take care of and regulate its own households, the government in the Village Law provides financial assistance in the form of Village Funds derived from a basic allocation fund of 90% which is the same amount for all villages then coupled with a Formulation Fund of 10% which becomes a nominal differentiator of village funds received. Formulation Funds are adjusted to the Number of Villagers (25%), The Number of Village Poor (35%), Village Area (10%) and geographical difficulty level (30%). Unfortunately, the division of parameters is consumptive and not productive, in the sense that there is no division of parameters for local potential villages that differ from one village to another. Therefore, the author initiated the idea in the form of the addition of village Local Potential parameters in the distribution of village fund formulation funds. The research methods used in this scientific work are normative juridical, using a statutory approach and a concept approach. The addition of Local Potential parameters in the distribution of Village Fund Formulation Fund includes the potential of the village tourism sector. With the implementation of this idea is expected to optimize tourism management efforts and increase the potential of the tourism sector in rural Indonesia.